2023
DOI: 10.1038/s41598-023-28852-1
|View full text |Cite
|
Sign up to set email alerts
|

Thioquinoline derivatives conjugated to thiosemicarbazide as potent tyrosinase inhibitors with anti-melanogenesis properties

Abstract: In the present study, a series of aryl-substituted thioqunoline conjugated to thiosemicarbazide were rationally designed and synthesized. The formation of target compounds was confirmed by spectral characterization techniques such as IR, 1H-NMR, 13C-NMR, ESI–MS, and elemental analysis. Among the synthesized derivatives, compound 10g bearing para-chlorophenyl moiety was proved to be the most potent tyrosinase inhibitor with an IC50 value of 25.75 ± 0.19 µM. Compound 10g as the most potent derivative exhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Molecular dynamics simulations were performed using Desmond from the Schrodinger Maestro interface (10), based on the results of the previous docking stage. An orthorhombic cell was de ned and lled with TIP3P model water molecules, and adequate Na ions were added to the system to neutralize the overall charge of the complex.…”
Section: Molecular Dynamicmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular dynamics simulations were performed using Desmond from the Schrodinger Maestro interface (10), based on the results of the previous docking stage. An orthorhombic cell was de ned and lled with TIP3P model water molecules, and adequate Na ions were added to the system to neutralize the overall charge of the complex.…”
Section: Molecular Dynamicmentioning
confidence: 99%
“…Synthetic and natural products containing quinoline structure representing diverse pharmacological activities such as anti-biotic [1], anti-cancer [2], anti-fungal [3], anti-malarial [4], anti-bacterial [5], anti-HIV [6], anti-rheumatoid arthritis [7], anti-tuberculosis [8], anti-diabetic [9], anti-oxidant [10], antiin ammatory [11]. Introducing chloroquine as anti-malaria began a new era of quickly developing drugs like pamaquine, cipro oxacin, camptothecin, topotecan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen-containing compounds such as hydroxyquinolinone scaffolds are important structures found in many pharmaceutically active compounds with drug-like properties, which provide high-quality leads and compound libraries 11 , 12 . They are structurally diverse and possess a variety of biological activities such as anticancer, antimicrobial 13 , metal chelator 14 , antialzheimer 15 , and antifungal activities 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Relying on its biological and structural properties for cell penetration, tFNA can adopt lower electrostatic repulsion to enter cells through cavernous protein internalization 36,41–43 . Further studies have also found that tFNA can pass through the skin barrier smoothly through skin attachments and has a high tissue penetration capacity 31 . Thus tFNA can reach deep tissues in a non‐invasive manner.…”
Section: Introductionmentioning
confidence: 99%